2022
DOI: 10.3389/fpls.2022.896421
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Synthesis and Metabolism During the Fruit Development in Hickory (Carya cathayensis)

Abstract: Hickory (Carya cathayensis) kernel is rich in powerful bioactive flavonoids, which can remove excess free radicals in the human body and play an important role in regulating the physiological metabolism of the plant. This study investigated the changes of flavonoids in hickory exocarp and embryo during development. In this study, 72 DEGs involved in the regulation of flavonoid biosynthesis in fruits were identified, and TT4, CCoAOMT1, UGT71D1, C4H, F3H, TT8, FLS1, and LDOX were identified as the core genes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The key genes involved in flavonoid biosynthesis were identified by stage-specific transcriptomic analysis in the petals of Camellia nitidissima (Liu et al, 2023). Changes in the key genes and flavonoid metabolites were also investigated using metabolomics and transcriptomics in the developing exocarp and embryo of hickory (Chen et al, 2022). Metabolomics examines the overall metabolic profile of plant samples through high-throughput detection and data processing (Foito and Stewart, 2018) and can thus provide a reliable method for investigating compounds contributing to the flavor of the persimmon fruit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The key genes involved in flavonoid biosynthesis were identified by stage-specific transcriptomic analysis in the petals of Camellia nitidissima (Liu et al, 2023). Changes in the key genes and flavonoid metabolites were also investigated using metabolomics and transcriptomics in the developing exocarp and embryo of hickory (Chen et al, 2022). Metabolomics examines the overall metabolic profile of plant samples through high-throughput detection and data processing (Foito and Stewart, 2018) and can thus provide a reliable method for investigating compounds contributing to the flavor of the persimmon fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid biosynthesis is complicated and diverse and requires the substrates derived from the phenylpropanoid pathway (Liu et al, 2021). Phenylpropanoid biosynthesis, flavonoid biosynthesis, flavone and flavonol biosynthesis, phenylalanine metabolism, isoflavone biosynthesis, and anthocyanin biosynthesis were observed to be enriched during the development of hickory fruit (Chen et al, 2022). In this study, a full-spectrum metabolomic determination of persimmon fruit was performed using liquid chromatography and triple quadrupole mass spectrometry in the MRM mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its exocarp and seeds contain rich flavonoids with anticancer, antibacterial, and anti-aging properties [ 24 ]. Based on previous transcriptome data of exocarp and seeds of Carya cathayensis , CcMYB12 was shown to co-express with some flavonoid-synthesis-related genes [ 25 ]. Based on 123 R2R3 - MYB s in Arabidopsis thaliana , 153 genes of the Carya cathayensis genome were searched, 115 of which were classified into 23 subgroups, and 38 were undivided according to the conservation of the N-terminal MYB domain and the C-terminal motif ( Figure 1 a), which agrees with the previous classification [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that flavonoids in the green exocarp and seeds of hickory have anticancer, antibacterial, and anti-aging properties [ 24 ]. Furthermore, the transcriptome of exocarp and seeds of Carya cathayensis were sequenced, and a co-expression network was constructed, showing that CcMYB12 is co-expressed with some flavonoid-synthesis-related genes [ 25 ]. Previous studies have also shown that MYB12 is involved in the formation of flavonols in Arabidopsis thaliana , Camellia sinensis , Lilium brownii , and Myrica rubra Sieb [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%